Comprendiendo la conducta del paciente con diabetes: estrategias para mejorar la adherencia terapéutica - Villalba-Arias , Jorge; Almi´rón-Santacruz, José; Torales, Julio (Medicina Clínica y Social, 2021)
Diabetes is a chronic disease that, if not treated properly, is accompanied by many comorbidities, complications, poor quality of life, as well as the possibility of a fatal outcome. Lack of therapeutic adherence is a barrier to overcome in order to improve the quality of life and health of affected patients. In this article a narrative review is made of the concepts on which therapeutic adherence is based, explaining the models on which grief sustains in the face of a chronic or terminal illness, summarizing the concepts that make the importance of communication, of the construction of therapeutic behaviors, of motivation-action and of emotions in health, all of which are part of the construct known as “therapeutic adherence”. Finally, succinct recommendations are presented to improve adherence, involving both the patient and the physician in its development, in order to increase therapeutic success.